The reliability of back-extrapolation in estimating V˙O2peak in different swimming performances at the severe-intensity domain - Massini, Danilo Alexandre; Simionato, Astor Reis; Almeida, Tiago André Freire; Macedo, Anderson Geremias; Espada, Mário Cunha; Reis, Joana Filipa; Besone Alves, Francisco; Pessôa Filho, Dalton Müller (Frontiers in Physiology, 2022)
The amount of anerobic energy released during exercise might modify the initial phase of oxygen recovery (fast-O2debt) post-exercise. Therefore, the present study aimed to analyze the reliability of peak oxygen uptake (V˙O2peak) estimate by back-extrapolation (BE−V˙O2peak) under different swimming conditions in the severe-intensity domain, verifying how the alterations of the V˙O2 recovery profile and anerobic energy demand might affect BE−V˙O2peak values. Twenty swimmers (16.7 ± 2.4 years, 173.5 ± 10.2 cm, and 66.4 ± 10.6 kg) performed an incremental intermittent step protocol (IIST: 6 × 250 plus 1 × 200 m, IIST_v200m) for the assessment of V˙O2peak. The V˙O2 off-kinetics used a bi-exponential model to discriminate primary amplitude, time delay, and time constant (A1off, TD1off, and τoff) for assessment of fast-O2debt post IIST_v200m, 200-m single-trial (v200 m), and rest-to-work transition at 90% delta (v90%Δ) tests. The linear regression estimated BE−V˙O2peak and the rate of V˙O2 recovery (BE-slope) post each swimming performance. The ANOVA (Sidak as post hoc) compared V˙O2peak to the estimates of BE−V˙O2peak in v200 m, IIST_v200 m, and v90%Δ, and the coefficient of dispersion (R2) analyzed the association between tests. The values of V˙O2peak during IIST did not differ from BE−V˙O2peak in v200 m, IIST_v200 m, and v90%Δ (55.7 ± 7.1 vs. 53.7 ± 8.2 vs. 56.3 ± 8.2 vs. 54.1 ± 9.1 ml kg−1 min−1, p > 0.05, respectively). However, the V˙O2peak variance is moderately explained by BE−V˙O2peak only in IIST_v200 m and v90%Δ (RAdj2 = 0.44 and RAdj2 = 0.43, p < 0.01). The TD1off and τoff responses post IIST_v200 m were considerably lower than those in both v200 m (6.1 ± 3.8 and 33.0 ± 9.5 s vs. 10.9 ± 3.5 and 47.7 ± 7.9 s; p < 0.05) and v90%Δ ( 10.1 ± 3.8 and 44.3 ± 6.3 s, p < 0.05). The BE-slope post IIST_v200m was faster than in v200 m and v90%Δ (-47.9 ± 14.6 vs. -33.0 ± 10.4 vs. -33.6 ± 13.8 ml kg−1, p < 0.01), and the total anerobic (AnaerTotal) demand was lower in IIST_v200 m (37.4 ± 9.4 ml kg−1) than in 200 m and 90%Δ (51.4 ± 9.4 and 46.2 ± 7.7 ml kg−1, p < 0.01). Finally, the τ1off was related to AnaerTotal in IIST_v200m, v200 m, and v90%Δ (r = 0.64, r = 0.61, and r = 0.64, p < 0.01). The initial phase of the V˙O2 recovery profile provided different (although reliable) conditions for the estimate of V˙O2peak with BE procedures, which accounted for the moderate effect of anerobic release on V˙O2 off-kinetics, but compromised exceptionally the V˙O2peak estimate in the 200-m single trial.